Calculating an Exceptional Machine - Hutton, Graham; Wright, Joel (2005)
In previous work we showed how to verify a compiler for a small language with exceptions. In this article we show how to calculate, as opposed to verify, an abstract machine for this language. The key step is the use of Reynold's defunctionalization, an old program transformation technique that has recently been rejuvenated by the work of Danvy et al.